Historical memory and the dialogue of cultures in the context of Georgian-Russian interaction - Sulaberidze, Yu. S. (Гуманитарные и юридические исследования, 2024)
Introduction. The modern history of Georgian-Russian relations is marked by relapses of the Cold war. The dividing line between nations has passed, with a centuries-old history of relationships. The article analyzes a complex of reasons causing mutual misunderstanding between states and peoples, who made a significant contribution to the development of world civilization. It is noted that the modern process of Georgian-Russian relations is significantly influenced by the legacy of the past, its interpretation by representatives of the intellectual community and the ruling elites. It is shown that in addition to this, deep culture, which preserves the civilizational and cultural layers of centuries-old interactions, also has a significant influence on the Georgian-Russian dialogue. Materials and Methods. The work is based on the principles of historicism, objectivity, scientific character, a comparative-historical, cultural-civilizational approach to the analysis of Georgian-Russian relations was used. The article is written on the basis of archival materials from the Central Historical Archive of Georgia, which preserves the historical memory of the origin and development of Georgian-Russian relations. Criticism of modern interpretations in the studies of Georgian historians is also given. Analysis. The analysis of modern research shows that the history of Georgian-Russian relations has undergone revision and transformation, the ideologeme of negativism dominates in the perception of relations. The emphasis is on the imperial, colonialist policy of the Russian Empire, the period of the USSR, as well as modern Russia in relation to Georgia. Political myths are created; the politicization of history highlights the negative aspects of relationships and creates obstacles to the search for a dialogue of cultures. Thus, those civilizational and cultural layers that were created over centuries of relationships are ignored. Results. The author argues that overcoming political myths will create conditions that will ensure the normalization of relations between countries, return Russia to the role of spiritual mediator in the Caucasus region, and Georgia to its worthy place in the community of democratic states of the Caucasus.